Penerapan Strategi Pendekatan Pada Pembelajaran SLB-C St Lusia Medan - Sinaga, Roberta Repina; Berutu, Sahira; Siantar, Imel Yolanda Lumban; Gaol, Dormauli Lumban; Sipayung, Jhon Rapindo; Gaol, Saurtua Van Mauricis Lumban; Panjaitan, Wiwi Roito (Lumbung Pare Cendekia, 2024)
Observation of learning at Special Schools (SLB) Phase C aims to understand the education process for children with special needs, especially intellectual disabilities. This research was conducted at SLB-C Santa Lusia using observation, interview, and document analysis methods. The results of the observation show that learning is adjusted to the individual abilities of students through the independent curriculum. The teaching methods used include self-guided learning and self-development, and assessments are carried out objectively to measure student progress. These findings are in line with the views of experts who emphasize the importance of a flexible approach in special education. Recommendations to improve learning effectiveness include the development of innovative methods and increased collaboration between teachers and parents.